Response of second ratoon lowland rice (Oryza sativa L.) to NK fertilizers at different levels of K application - M. Baňoc , Dionesio; Imperial, Rico Mark (Journal of Pure and Applied Agriculture, 2023)
Granular fertilizers are effective nutrient materials for boosting crop yield in counteracting the possible low productivity problems caused by climate change. This study aimed to determine the response of second ratoon rice plants to nitrogen and potassium (NK) fertilizers at the different levels of potassium (K) application. Choose an NK fertilizer combination that provides a high ratoon yield, and evaluate the profitability of blending N and K fertilizers at different rates of K application. A Randomized Complete Block Design (RCBD) was adopted in establishing the experiment consisting of three replications and six treatments: T0 = unfertilized control, T1 = 120 - 60 - 60 kg ha-1 N, P2O5, K2O, T2 = 120 kg ha-1 N, T3 = 120 kg ha-1 N + 20 kg ha-1 K2O, T4 = 120 kg ha-1 N + 40 kg ha-1 K2O, and T5 = 120 kg ha-1 N + 60 kg ha-1 K2O. The ratooned plants applied with 120 kg ha-1 N + 60 kg ha-1 K2O (T5) significantly emanated the tallest plant height, more number of tiller hill-1 , greater leaf area index (LAI), higher fresh straw yield, longer panicle length, abundant production of spikelets per panicle and produced remarkable productivity compared to unfertilized control. This option obtained a higher gross margin (USD 848.30) similar to T4 plants which achieved the highest gross margin of USD 866.28, due to lower variable cost incurred in applying K fertilizer. Therefore, T4 is a feasible and cost-reducing fertilization strategy in providing higher profitability amidst climate change situations. © 2021 Department of Agricultural Sciences, AIOU